1998
DOI: 10.1046/j.1360-0443.1998.93689511.x
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity, personality disorders and pathological gambling severity

Abstract: Results show elevated traits of impulsivity among clinic samples of pathological gamblers compared to normative data and show that impulsivity is related to the severity of gambling behaviour as measured by the South Oaks Gambling Questionnaire. A principal component analysis of the Eysenck Impulsivity Scale and the personality Disorder Questionnaire-Revised, demonstrated that the concept of the "antisocial-impulivist" identified to Blaszczynski, Steel & McConaghy (1997) is not only characterized by impulsivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
1
16

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(118 citation statements)
references
References 19 publications
11
90
1
16
Order By: Relevance
“…Such a finding is consistent with recent work on the role of brain reward circuitry in PG, ADHD, as well as other psychiatric disorders like substance abuse and major depression (Chau et al, 2004), and is highly consistent with other research, supporting the role of impulsivity in mediating the severity of gambling behavior (Chambers and Potenza, 2003;Steel and Blaszczynski, 1998). PG has been indeed associated to the impulsive subtype of ADHD in several clinical-epidemiology studies.…”
Section: Impulsivity and Risk Pronenesssupporting
confidence: 78%
“…Such a finding is consistent with recent work on the role of brain reward circuitry in PG, ADHD, as well as other psychiatric disorders like substance abuse and major depression (Chau et al, 2004), and is highly consistent with other research, supporting the role of impulsivity in mediating the severity of gambling behavior (Chambers and Potenza, 2003;Steel and Blaszczynski, 1998). PG has been indeed associated to the impulsive subtype of ADHD in several clinical-epidemiology studies.…”
Section: Impulsivity and Risk Pronenesssupporting
confidence: 78%
“…In their analysis of the NESARC data, Petry (2005) and colleagues identified increased odds of Paranoid and Schizoid Personality Disorders among individuals with PGD. Earlier research has also reported high percentages of the Cluster A and Cluster C disorders among treatment seeking gamblers (Steel & Blaszczynski, 1998). Various researchers have identified a relationship between Cluster C diagnoses and PGD in treatment samples (Specker et al, 1996;Steel et al, 1998), particularly for Avoidant Personality (Specker et al, 1996) and Obsessive-Compulsive Personality Disorder (Black & Moyer, 1998).…”
Section: Pathological Gambling and Personality Disordersmentioning
confidence: 99%
“…Earlier research has also reported high percentages of the Cluster A and Cluster C disorders among treatment seeking gamblers (Steel & Blaszczynski, 1998). Various researchers have identified a relationship between Cluster C diagnoses and PGD in treatment samples (Specker et al, 1996;Steel et al, 1998), particularly for Avoidant Personality (Specker et al, 1996) and Obsessive-Compulsive Personality Disorder (Black & Moyer, 1998). For example, in a study of psychiatric outpatients, Henderson (2004) found that those with PGD displayed elevated scores on Avoidant, Compulsive, and Self-Defeating Personality Scales.…”
Section: Pathological Gambling and Personality Disordersmentioning
confidence: 99%
“…Impulsivity is an important component in PG [27]. Many studies have found that Pathological gamblers score higher on impulsivity [28]. A number of events like anti-social behaviour, personality disorder; attention deficit hyperactive disorder (ADHD) are some of the syndromes associated with PG.…”
Section: Phenomenology Of Pathological Gamblingmentioning
confidence: 99%